The Role of the Learning Environment and Improving Academic Performance Through Reading Interest - Etty Umamy (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Many students have not mastered the Indonesian language well, as evidenced by their daily test scores, which mostly fall in the middle to lower categories. This phenomenon is intriguing to explore in the context of improving student learning achievement. Therefore, this study aims to analyze the influence of the learning environment on Indonesian language learning achievement, with reading interest as the mediator. This research employs a quantitative method with a population of 815 students who have taken the Indonesian language course. With a margin of error of 5%, the sample size selected is 262 students. The analysis is conducted using Structural Equation Modeling (SEM). The research findings indicate that Indonesian language learning achievement improves due to the positive influence of the school environment and reading motivation, which contributes to students' reading interest. Reading interest has been proven to mediate the influence of the school environment on learning achievement. The implications of this study are that a conducive learning environment and collaboration among teachers, parents, and the community are crucial to support students in reaching their maximum potential. This also impacts the enhancement of students' reading interest and learning achievement.